Electrochemical Characteristics of Mg-3al-1Zn Magnesium Alloy Surface with Hydroxyapatite Coating - Filip Pastorek; Branislav Hadzima; Pavel Dolezal (Communications - Scientific letters of the University of Zilina, 2012)
Electrochemical characteristics of Mg-3Al-1Zn alloy surfaces after grinding and/or coating by hydroxyapatite were investigated by voltamperometric tests in 0.9 % NaCl solution. The hydroxyapatite treatments were realised by electrochemical method in water solution of Ca(NO3)2 . 4H2O, (NH4)2HPO4 and H2O2 . The influences of various types of hydroxyapatite treatment processes on corrosion potentials, corrosion current densities and characteristics of passive state were evaluated. Basic potentiodynamic curves obtained from the electrochemical tests were analysed by Tafel analyses. The improvement of short-time electrochemical behaviour after hydroxyapatite treatment of tested alloy surface was reported.